Družni govor cinizma in metafizike - Hedžet Tóth, Cvetka (Slavistična revija, 2006)
The article discusses some viewpoints of the contemporary German philosopher Peter Sloterdijk, particularly the ones related to the stagnation of theory after the end of the student movement. The uneasiness of culture in the post-modern era is related to the growing level of cynicism and the proclivity for nihilism. According to Sloterdijk, this ia s consequence of the overly emphasized historicism that had developed in the 19th century. The theory became depressing and melancolic after the permanent werainess of life had se in; Nietzsche had been compelled to point out the harmful effect of history on life. With the help of ancient Greek models Sloterdijk attempts to make the theory aware that it must be well-intentioned and cultivate the sense of happiness. Ancient theory creates serenity, while modern theory creates confusion and insanity. After the symbolic year 1989, when it became increasingly evident how the idea of world history had been exhausted, he first attempted to dispute the political addiction of his ear with the life itself. The authenticity of life is what is in question, which is, according to Sloterdijk's political anthropology, lacking in politics, i.e., life has been robbed of all its spontaneity.
Keywords: anthropology of politics; antropologija politike; ethics; etika; filozofija; filozofija zgodovine; metafizika; metaphysics; philosophy; philosophy of history; Sloterdijk, Peter; utopia; utopija